If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 8 = 2y + -6 Reorder the terms: 8 + 4y = 2y + -6 Reorder the terms: 8 + 4y = -6 + 2y Solving 8 + 4y = -6 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 8 + 4y + -2y = -6 + 2y + -2y Combine like terms: 4y + -2y = 2y 8 + 2y = -6 + 2y + -2y Combine like terms: 2y + -2y = 0 8 + 2y = -6 + 0 8 + 2y = -6 Add '-8' to each side of the equation. 8 + -8 + 2y = -6 + -8 Combine like terms: 8 + -8 = 0 0 + 2y = -6 + -8 2y = -6 + -8 Combine like terms: -6 + -8 = -14 2y = -14 Divide each side by '2'. y = -7 Simplifying y = -7
| -4x^2+5x+100=0 | | X^2=.064 | | 3(5-3t)+5t=-2t-7 | | 15x+12x+17=180 | | 13-2n=4+n | | 2x^4+3x^3-4x^2-x+14=0 | | 4y+2-y=6 | | 2x+5(x-10)=-1 | | 3(5x+2)-(9x-8)=7(x+12) | | 2x^4+3x^3-4x^2-x+14=-12 | | 3x-2=18-2x | | -2x+5(x-10)=-1 | | 5(5-1)+-3125-7= | | 3b^2+5b= | | 5x^4+4x^3= | | 5r+3f=12 | | 20-12=4(x-1) | | (x-3)(2x-5)+6=2x^2-12 | | -6x-2=4x-1 | | 18w-2-10w+14= | | 6p^4-486p^2= | | 9x^2+27x-7=0 | | 12x^2-6x-3=3-5x | | f(x)=2x^2+20x+49 | | sin(2x-30)=cos(3x+5) | | (-7-3m^3-3m^4)+(-8m-8m^3-m^4)= | | 4z=16-40 | | 4p+6-2p+3= | | x+8*2x-4=1008 | | 2/3x36 | | Jp=1/2 | | -5x^3-2x^2+7x= |